2008
DOI: 10.1038/jcbfm.2008.140
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Vagus Nerve Mediates the Protective Effects of Melanocortins against Cerebral and Systemic Damage after Ischemic Stroke

Abstract: A vagus nerve-mediated, efferent cholinergic protective pathway activated by melanocortins is operative in circulatory shock and myocardial ischemia. Moreover, melanocortins have neuroprotective effects against brain damage after ischemic stroke. Here we investigated cerebral and systemic pathophysiologic reactions to focal cerebral ischemia in rats induced by intrastriatal microinjection of endothelin-1, and the possible protective role of the melanocortin-activated vagal cholinergic pathway. In the striatum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 41 publications
3
45
1
Order By: Relevance
“…Thus, our data suggest that cerebral ischemia enhances the parasympathetic tone. A recent study demonstrated that the vagus nerve mediates the anti-inflammatory and neuroprotective effect of a melanocortin derivative after cerebral ischemia (Ottani et al, 2008). Thus, the enhanced parasympathetic tone supported by our data may indicate an endogenous neuroprotective process.…”
Section: Heart Ratementioning
confidence: 54%
“…Thus, our data suggest that cerebral ischemia enhances the parasympathetic tone. A recent study demonstrated that the vagus nerve mediates the anti-inflammatory and neuroprotective effect of a melanocortin derivative after cerebral ischemia (Ottani et al, 2008). Thus, the enhanced parasympathetic tone supported by our data may indicate an endogenous neuroprotective process.…”
Section: Heart Ratementioning
confidence: 54%
“…These endogenous peptides and their synthetic analogs play roles in protecting the body against various diseases, such as hemorrhagic shock, intestinal ischemia, ischemic stroke, and traumatic brain injury [10e12]. Previous studies have shown that the melanocortin-4 (MC4) receptor can play an antishock role via the vagus nervemediated cholinergic pathway [11,13] in a self-defense antiinflammatory mechanism that activates (as the main final step) the a7-acetylcholine receptor subunit on inflammatory cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There are several other potential VNS clinical applications, reasoning from the known role of the vagus, including obesity (Roslin and Kurian, 2001), craving (Bodenlos et al, 2007), pain (Borckardt et al, 2006a(Borckardt et al, , 2005, traumatic brain injury (Colombo et al, 2008;Neese et al, 2007;Ottani et al, 2009), and anxiety (George et al, 2008b). These small sample size trials all suggest potential efficacies in these domains but RCT are needed.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…There is also intense recent work investigating the role that VNS might have on inflammation and the immune response (Ottani et al, 2009;Pavlov, 2008;Van Der Zanden et al, 2009). …”
Section: Research Usesmentioning
confidence: 99%